Enhanced airway sensory nerve reactivity in non-eosinophilic asthma - Richard Beasley; Neil Pearce; Jeroen Douwes; Julian Crane; Peter Gibson; Collin Brooks; STEPHEN HOLGATE; Hajar Ali; Philip Pattemore; Yu-Chieh Tzeng; Thorsten Stanley (BMJ Open Respiratory Research)
Background Neural mechanisms may play an important role in non-eosinophilic asthma (NEA). This study compared airway sensory nerve reactivity, using capsaicin challenge, in eosinophilic asthma (EA) and NEA and non-asthmatics.Methods Thirty-eight asthmatics and 19 non-asthmatics (aged 14–21 years) underwent combined hypertonic saline challenge/sputum induction, fractional exhaled nitric oxide, atopy and spirometry tests, followed by capsaicin challenge. EA and NEA were defined using a sputum eosinophil cut-point of 2.5%. Airway hyperreactivity was defined as a ≥15% drop in FEV1 during saline challenge. Sensory nerve reactivity was defined as the lowest capsaicin concentration that evoked 5 (C5) coughs.Results Non-eosinophilic asthmatics (n=20) had heightened capsaicin sensitivity (lower C5) compared with non-asthmatics (n=19) (geometric mean C5: 58.3 µM, 95% CI 24.1 to 141.5 vs 193.6 µM, 82.2 to 456.0; p<0.05). NEA tended to also have greater capsaicin sensitivity than EA, with the difference in capsaicin sensitivity between NEA and EA being of similar magnitude (58.3 µM, 24.1 to 141.5 vs 191.0 µM, 70.9 to 514.0) to that observed between NEA and non-asthmatics; however, this did not reach statistical significance (p=0.07). FEV1 was significantly reduced from baseline following capsaicin inhalation in both asthmatics and non-asthmatics but no differences were found between subgroups. No associations with capsaicin sensitivity and atopy, sputum eosinophils, blood eosinophils, asthma control or treatment were observed.Conclusion NEA, but not EA, showed enhanced capsaicin sensitivity compared with non-asthmatics. Sensory nerve reactivity may therefore play an important role in the pathophysiology of NEA.